If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1 + -3a) = 20 + 4a (1 * 4 + -3a * 4) = 20 + 4a (4 + -12a) = 20 + 4a Solving 4 + -12a = 20 + 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. 4 + -12a + -4a = 20 + 4a + -4a Combine like terms: -12a + -4a = -16a 4 + -16a = 20 + 4a + -4a Combine like terms: 4a + -4a = 0 4 + -16a = 20 + 0 4 + -16a = 20 Add '-4' to each side of the equation. 4 + -4 + -16a = 20 + -4 Combine like terms: 4 + -4 = 0 0 + -16a = 20 + -4 -16a = 20 + -4 Combine like terms: 20 + -4 = 16 -16a = 16 Divide each side by '-16'. a = -1 Simplifying a = -1
| 10x-4y=8 | | 4m+2+m=23 | | 5x-7=25x+1 | | -5x-x+3=-3x+x-21 | | -56=21y | | 3(3x-1)=3x+2 | | 0.25x+7=.33x-8 | | -4x+5(x+3)+6=-5(x+3) | | 8-8x=104-29x | | -4(3n+3)+4(10-4n)=-7n+7n | | 5r-3=13r+11 | | 12a^2+36ap+27p^2=0 | | 62x+5x-2=10 | | 7.5x=25.50 | | 8x+10=5x+12-2 | | y=3[x-(7-x)]-5(x+1) | | -n+4(1+7n)=-15+8n | | 64=-16t^2+64t+64 | | p-1=5p+3p-3 | | -6=4-z-z | | 7.6x-4.9x=-81 | | 10-6x=-4(x-2)+6 | | 9x^2+4x-2=0 | | 0.40x+0.006(30)=9.8 | | -3(z+1)=-5(z-1) | | 10x+5y=6 | | 7y+y=-16 | | 3x+13y=15 | | 5y-8-2y=-4y+13 | | 8-2x-15x^2=0 | | 3+4(z+5)=23 | | 12x^2-xy-y^2=0 |